Exploring teacher development strategies in four most popular Kampung Inggris language courses: A descriptive analysis - Rochastuti, Laras Ati; Hamamah, Hamamah; Rohmah, Zuliati (ARKA INSTITUTE, 2024)
Teacher development programs have been commonly done for teachers in formal language learning contexts, meanwhile in non-formal contexts, such as language courses, the teacher development program has not yet been widely known, despite the variety of benefits that teacher development programs give to teachers. Thus, this research analyzes the teacher development program in Kampung Inggris language courses through qualitative studies using interviews with nine teachers from four language courses. Results suggest that teacher development programs in the four language courses can be categorized into skill learning, sharing, and mentoring. Skill learning includes drilling, evaluation, and e-courses while sharing and mentoring involve peer-teacher sharing programs and consultation with CELTA-certified teachers The findings also indicated that teachers still need more teacher development programs that are not yet given by the language courses management. Thus, the study suggests further analysis of this issue and more opportunities for teachers in non-formal language learning programs to develop their teaching skills.